Roger Callois og det Hellige - Hommelgaard, Erling (Religionsvidenskabeligt Tidsskrift, 1986)
This article introduces the French sociologist etc. Roger Callois. The article’s main focus is on comparative religion, i.e. the early part of Callois’ authorship, based on his work with Collège de sociologie, which he formed in collaboration with Georges Bataille in the late thirties. Dedicated to the socalled “sociology of the sacred”, they developed the concepts of the sacred and the profane as a basis for explaining rituals in religious life. With a background in 19th century hypotheses on totemism and Durkheimian analyses of elementary forms of religious life, Callois and Bataille examine the constitution of communal life. They maintain that rituals must be taken into consideration, when the formation of societies is to be described. This means that the theories of the sacrificial are put forward. Callois also treats the structure of prohibition in primitive religion as a protection against the confusion of the sacred and the profane. But the prohibitions must also b e seen in relation to the transgression, stressing what Callois exposes in his “theory of feasts” that the feast must be seen as a kind of doubling up the sacrifice, and therefore essentially an excess. Elaborating the Maussian thesis that “it is obligatory to believe in the myths”, Callois speaks about the “affective necessities” of the myth. By this he means the ability of the myths to evoke affects and feelings, often inimical to society, but also to catch these affects and lead them to satisfaction, thus encapsulating the myth with social coercion. Callois demonstrates this in the famous analysis of the praying mantis. Furthermore, Callois addresses the relationship between myth and ritual, using the Bergsonian formula of the myth as a substitution for the animal instincts evoking real behaviour in the way that the representations of the myth virtually evoke similar behaviour in human life. Moreover the function of the ritual is to perform in reality what the myth stages virtually.